2018
DOI: 10.1016/j.ajem.2017.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Safety events in pediatric out-of-hospital cardiac arrest

Abstract: Safety events were common during pediatric OHCA resuscitation especially in the domains of medications, airway/breathing, and arrest algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 24 publications
1
24
1
1
Order By: Relevance
“…Seven studies were in trauma patients (n = 500) [21,26,34,[39][40][41]44], six in arrested patients (n = 804) [5,17,25,29,33,38], and three in head injury patients (n = 414) [6,31,37], and the remaining studies comprised a mixed population of all patients requiring airway management (n = 9849). There was no association between team composition and type of paediatric patients treated (P = 0.875).…”
Section: Outcomes By Clinical Populationmentioning
confidence: 99%
“…Seven studies were in trauma patients (n = 500) [21,26,34,[39][40][41]44], six in arrested patients (n = 804) [5,17,25,29,33,38], and three in head injury patients (n = 414) [6,31,37], and the remaining studies comprised a mixed population of all patients requiring airway management (n = 9849). There was no association between team composition and type of paediatric patients treated (P = 0.875).…”
Section: Outcomes By Clinical Populationmentioning
confidence: 99%
“…found, in eight simulated paediatric resuscitation scenarios, that four 10‐fold errors occurred. Hansen et al . performed a retrospective analysis of 35 paediatric out‐of‐hospital cardiac arrests, which found that 20% of patients were given a 10‐fold overdose of adrenaline.…”
Section: Need For Significant Dose Calculation and Manipulation Undermentioning
confidence: 99%
“…Resuscitation events are chaotic and stressful to many participants leading to multiple opportunities for errors. Errors during cardiac arrest management are common, with pediatric patients particularly susceptible due to the relative infrequency of pediatric cardiac arrests and wide-ranging patient weights and sizes necessitating more complex life support algorithms (defibrillation doses, medication doses, range of CPR quality goals) (43)(44)(45)(46)(47)(48). Clear evidence exists that the delivery of high quality chest compressions and rapid medication administration improves short-and longterm outcomes after cardiac arrest (49,50), however repeated studies show that the CPR delivered at the bedside does not meet guideline recommendations (51,52).…”
Section: Improving the Quality Of Cardiopulmonary Resuscitationmentioning
confidence: 99%